2010
DOI: 10.1107/s0021889810012197
|View full text |Cite
|
Sign up to set email alerts
|

Coherent and diffuse X-ray scattering in crystals modulated by a surface acoustic wave

Abstract: Equations describing the coherent and diffuse scattering in a crystal modulated by a surface acoustic wave (SAW) are derived using the dynamical X‐ray diffraction theory. The effect of depth attenuation of the Rayleigh surface wave amplitude on the crystal rocking curve profiles is investigated. Results of the numerical simulation of the dynamical diffraction in a mosaic crystal modulated by a SAW, taking into account a block size distribution, are presented. It is shown that the diffuse scattering is distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 41 publications
1
37
0
Order By: Relevance
“…The procedure for deriving the equations describ ing X ray diffraction by a laterally modulated crystal in triple crystal diffractometry is described in detail in [14]. It was shown that if a plane X ray wave is incident on the crystal, the diffracted beam has a nonzero amplitude for the values of q x that are multiples of the wavenumber κ s of the lateral modulation (i.e., for val ues of = nκ, where n = 0, ±1, ±2, … are the numbers of diffraction orders).…”
Section: Crystal Lattice Modulation By An Acoustic Wavementioning
confidence: 99%
See 2 more Smart Citations
“…The procedure for deriving the equations describ ing X ray diffraction by a laterally modulated crystal in triple crystal diffractometry is described in detail in [14]. It was shown that if a plane X ray wave is incident on the crystal, the diffracted beam has a nonzero amplitude for the values of q x that are multiples of the wavenumber κ s of the lateral modulation (i.e., for val ues of = nκ, where n = 0, ±1, ±2, … are the numbers of diffraction orders).…”
Section: Crystal Lattice Modulation By An Acoustic Wavementioning
confidence: 99%
“…Using the boundary conditions, we can write the solution for a Rayleigh surface wave in the form [14,16] (1)…”
Section: Crystal Lattice Modulation By An Acoustic Wavementioning
confidence: 99%
See 1 more Smart Citation
“…X ray diffraction, which is highly sensitive to lattice strain, is successfully used to study acoustic waves in near surface layers of crystals [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. The specific features of SAW propagation in solids were monitored by X ray topography [3][4][5], grazing X ray diffraction [6,7], and double and triple crystal X ray diffraction [8][9][10][11][12][13][14][15][16][17]. Various effects accompanying X ray scattering in SAW modulated crystals were described in terms of the dynamical [11][12]18] and kinematical [10,13,19] diffraction theories.…”
Section: Introductionmentioning
confidence: 99%
“…Different materials, such as LiNbO 3 , have been used as a carrier of the SAWs in different crystallographic geometries (Roshchupkin et al, 1992(Roshchupkin et al, , 1998Tucoulou et al, 2001). Appropriate theoretical models have been developed for the explanation of diffraction properties, especially the dependence of the diffracted intensity on the amplitude of the high-frequency signal applied to the device for the SAWs' excitation (Punegov et al, 2010;Schelokov et al, 2004). The first example of such a device was reported by Tucoulou et al (1997), who demonstrated for the first time the feasibility of a fast diffraction chopper for synchrotron radiation single-bunch pulses.…”
Section: Introductionmentioning
confidence: 99%